Adherence to the Mediterranean Diet and Lifestyle Characteristics of University Students in Cyprus: A Cross-Sectional Survey - Botsaris, George; Gekas, Vassilis; Panayiotou, Andrie; Hadjimbei, Elena (My University, 2016)
Objective. To assess dietary-related habits among young adults. Design and Setting. Dietary habits were assessed cross-sectionally, using a self-completed questionnaire in 193 students enrolled in public and private universities in Cyprus. Adherence to the Mediterranean diet was evaluated using the validated KIDMED index. BMI was estimated based on weight and height measurements. Results. The mean BMI was 23.31 (±3.98). The mean adherence score to the Mediterranean diet was 6.0 (IQR 4 to 8), with 26.9% of students being classified as high adherers and 21.8% as low adherers to the Mediterranean diet. About 32% of students consumed a second serving of fruit and vegetables more than once a day, whereas 26% reported going more than once a week to a fast-food restaurant and 31% consumed sweets and candy several times a day. On the other hand, 76% of participants reported consumption of at least two dairy products daily and 88% use olive oil at home. The majority consume coffee 2-3 times per day. Conclusions. Results support a shift from traditional healthy diets to more unhealthy eating patterns. However, we also report a high dairy intake and use of olive oil. Tailored-made strategies targeting the young adult population could be warranted.